Short Duration Small Sided Football and to a Lesser Extent Whole Body Vibration Exercise Induce Acute Changes in Markers of Bone Turnover. (29th November 2016) - Bowtell, J. L.; Jackman, S. R.; Scott, S.; Connolly, L. J.; Mohr, M.; Ermidis, G.; Julian, R.; Yousefian, F.; Helge, E. W.; Jørgensen, N. R.; Fulford, J.; Knapp, K. M.; et al.
Abstract : We aimed to study whether short-duration vibration exercise or football sessions of two different durations acutely changed plasma markers of bone turnover and muscle strain. Inactive premenopausal women (n = 56 ) were randomized to complete a single bout of short (FG15) or long duration (FG60) small sided football or low magnitude whole body vibration training (VIB). Procollagen type 1 amino-terminal propeptide (P1NP) was increased during exercise for FG15 (51.6 ± 23.0 to 56.5 ± 22.5   μ g·L −1, mean ± SD, P < 0.05 ) and FG60 (42.6 ± 11.8 to 50.2 ± 12.8   μ g·L −1, P < 0.05 ) but not for VIB (38.8 ± 15.1 to 36.6 ± 14.7   μ g·L −1, P > 0.05 ). An increase in osteocalcin was observed 48 h after exercise (P < 0.05 ), which did not differ between exercise groups. C-terminal telopeptide of type 1 collagen was not affected by exercise. Blood lactate concentration increased during exercise for FG15 (0.6 ± 0.2 to 3.4 ± 1.2  mM) and FG60 (0.6 ± 0.2 to 3.3 ± 2.0  mM), but not for VIB (0.6 ± 0.2 to 0.8 ± 0.4  mM) (P < 0.05 ). Plasma creatine kinase increased by 55 ± 63 % and 137 ± 119 % 48 h after FG15 and FG60 (P < 0.05 ), but not after VIB (26 ± 54 %, NS). In contrast to the minor elevation in osteocalcin in response to a single session of vibration exercise, both short and longer durations of small sided football acutely increased plasma P1NP, osteocalcin, and creatine kinase. This may contribute to favorable effects of chronic training on musculoskeletal health.